2015
DOI: 10.1523/jneurosci.1698-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

ComplementC3-Deficient Mice Fail to Display Age-Related Hippocampal Decline

Abstract: The complement system is part of the innate immune response responsible for removing pathogens and cellular debris, in addition to helping to refine CNS neuronal connections via microglia-mediated pruning of inappropriate synapses during brain development. However, less is known about the role of complement during normal aging. Here, we studied the role of the central complement component, C3, in synaptic health and aging. We examined behavior as well as electrophysiological, synaptic, and neuronal changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
301
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(336 citation statements)
references
References 57 publications
12
301
0
Order By: Relevance
“…Interestingly, higher spine density in pyramidal neurons has been reported in the temporal cortex of ASD patients than in controls [27]. In addition, aged C3 knock out mice performed better on learning and memory tests than aged WT mice [28]. A recent study has found increased C4 mRNA levels in postmortem brain samples from schizophrenia, and reduced synaptic pruning in mice lacking functional C4 [29].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, higher spine density in pyramidal neurons has been reported in the temporal cortex of ASD patients than in controls [27]. In addition, aged C3 knock out mice performed better on learning and memory tests than aged WT mice [28]. A recent study has found increased C4 mRNA levels in postmortem brain samples from schizophrenia, and reduced synaptic pruning in mice lacking functional C4 [29].…”
Section: Discussionmentioning
confidence: 99%
“…The complement cascade, a sequence of protein-protein interactions that “attacks” and damages cell membranes, may also be activated in the aging brain and is implicated in the pathogenesis of AD and ischemic stroke (Arumugam et al, 2009; Stephan et al, 2013; Hong et al, 2016). Genetic or pharmacological inhibition of the complement cascade can ameliorate synapse loss and neuronal death that occurs during normal aging and in mouse models of AD and stroke (Arumugam et al, 2007; Shi et al, 2015; Hong et al, 2016). In addition, activated microglia express an inducible form of NO synthase and produce large amounts of NO that can cause oxidative damage to neurons.…”
Section: Cellular and Molecular Hallmarks Of Brain Agingmentioning
confidence: 99%
“…Profound region-specific differences in C3-mediated age-dependent elimination of hippocampal CA synapses were recently reported, although the investigators did not address the role of reactive gliosis in this process (Shi et al, 2015). The mechanisms underlying CA region specific effects of C3a on astrocyte activation and the potentially distinct roles of C3b and C3a, the two products of C3 activation, in the hippocampus merit further investigation.…”
mentioning
confidence: 99%